2018
DOI: 10.31643/2018/6445.44
|View full text |Cite
|
Sign up to set email alerts
|

Modern condition and proposed solutions for processing chloride waste of titanium-magnesium production

Abstract: Рассмотрена проблема утилизации хлоридных отходов, образующихся при получении губчатого титана из ильменитовых концентратов в процессе Кроля и металлического магния электролизом из природного карналлита. Техногенные хлорсодержащие отходы представляют значительную опасность для окружающей среды, загрязняя почвы и природные воды при выбросах их в атмосферу, при сбросе образующихся кислых промышленных сточных вод в водные объекты, при размещении твердых отходов в шламохранилищах. Хлоридные отходы титанового произ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The process of shape change, which leads to the failure of reactors, is due to factors related to the consistent effect of the melt of magnesium chloride, metallic and liquid magnesium, vapor-forming titanium tetrachloride loaded into the reactor, on the one hand. And on the other hand, the effect of a temperature of 1000-1200 °C on the walls of the retort with the simultaneous interaction of the hot air of the furnace containing chlorine vapors [3,4]. As a result of research [7], it was found that the greatest wear of steel 10X18H10T is observed at the boundary of the gas phase with the melt in the zone of the exothermic reaction of titanium tetrachloride with magnesium.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…The process of shape change, which leads to the failure of reactors, is due to factors related to the consistent effect of the melt of magnesium chloride, metallic and liquid magnesium, vapor-forming titanium tetrachloride loaded into the reactor, on the one hand. And on the other hand, the effect of a temperature of 1000-1200 °C on the walls of the retort with the simultaneous interaction of the hot air of the furnace containing chlorine vapors [3,4]. As a result of research [7], it was found that the greatest wear of steel 10X18H10T is observed at the boundary of the gas phase with the melt in the zone of the exothermic reaction of titanium tetrachloride with magnesium.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The processes of shape change in such an aggressive environment have not been studied enough (as well as the "handling" of the retort material); another issue is the choice of material for the manufacture of retorts [9,10]. In addition, the optimal dimensions of the retorts and the influence of operating modes are also poorly understood [4].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…From the commercial perspective, the composition of the rare earth elements in the spent melt of titanium chlorinators (SMTC) is attractive, as the proportion of dysprosium is 57%, neodymium 8%, and cerium is 13% [ [39], [40]]. The authors of work [41] studied the recovery of REE concentrate from Thus, the authors proposed technological flow sheet recovery of REE concentrate from SMTC (figure 4). The results of chemical analysis showed that the content of REE oxalates was 96.0%, while the overall content of the main impurities such as barium and iron oxalates accounted for 3.1%.…”
Section: Introductionmentioning
confidence: 99%